The Concept of Tarkib Isnadi In Arabic Grammatical Thought and Its Equivalence In Indonesian: A Contrastive Analysis - Muhammad Lukman Arifianto (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Institut Agama Islam Darullughah Wadda'wah Pasuruan, 2020)
This paper aims to explain the concept of Tarkib Isnadi in Arabic grammar and describe the equivalent concept and its components in Indonesian grammar. In the realm of Arabic grammar, Tarkib Isnadi is a core component in the structure of clauses or sentences in Arabic. A good understanding of Tarkib Isnadi in Arabic and its equivalent in Indonesian will make it easier for Arabic learners (L2) who come from native Indonesian speakers (L1) to identify clause and sentence structures in various Arabic discourses. The methods used in data analysis in this study are distribution and identity-referential methods. Based on observations, it is found that the concept of Tarkib Isnadi in Arabic has a concept equivalent to a clause in Indonesian because both have the core constituents or pillars of the sentence. On the other hand, there are also some differences in the concept of Tarkib Isnadi in Arabic with the concept of clauses in Indonesian. The difference mainly lies in terms of the formation of the concept and the filling components of their syntactic functions.